KONSEP PERNIKAHAN DALAM PEMIKIRAN FUQAHA - Basri, Rusdaya (DIKTUM: Jurnal Syariah dan Hukum, 2015)
This article discussed the concept and purpose of marriage in the views of jurists. Based on primary sources of Islamic teachings, Al-Qurâan, the jurists agreed that the concept of marriage is a contract that gives legal permissibility avail to hold family relationships (husband-wife) between men and women, held mutual help, and put limits on the rights to their owners as well as the fulfillment of the obligations for each party. The purpose of marriage is concluded in some facilities: (1) Means to release sexual desires, (2) Means to find serenity (sakinah ma waddah), (3) Means to acquire and to hold offspring, and (4) Means to maintain themselves from moral damages.